Applied versus situated mathematics in Ancient Egypt : bridging the gap between theory and practice - Visokolskis, Aída Sandra (2019)
Fil: Visokolskis, Aída Sandra. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Escuela de Filosofía; Argentina.